Economics - Paul Oslington (St Andrews Encyclopaedia of Theology, 2023)
This article is about the relationship between economics and Christian theology. It is concerned with economics in the modern sense (distinguished from the ancient art of oikonomia or household management, and personal financial decision making). Economics is about systems of provision for human need and flourishing. Economics, in the modern sense, is a science, and there are strong analogies between the economics/theology dialogue and the science/theology dialogue. The dialogue with economics is in some ways more complex because economic systems are not just products of nature but of human design. Theodicy, for instance, is more fraught in the economic domain than the natural world. After a brief sketch of contemporary economics, this article begins with an examination of scriptural teaching on economic matters. Emphasis is placed on the larger economic themes of the scriptures (such as creation, providence, eschatology, redemption, reconciliation, divine economy) rather than passages dealing with specific economic controversies. It then considers the reception of this scriptural teaching in different times and places. History is the best way of learning about the relationship between theology and economics. The reception of scriptural teaching on economic matters is a diverse story, the only constant being the immense influence of such teaching on societies. Theology has influenced economic behaviour, systems, and economic ideas – including the formation of the science of political economy in Britain in the late eighteenth and early nineteenth centuries, and its spread to North America and other parts of the world. The influence of Christian ideas about economics continues even as church attendance declines across the West. The shape of Christian economic ideas in Asia, Africa, and Latin America is important to the future of these regions. The aim of the article is to increase understanding of what Christian faith means in the economic domain, and understanding of the diverse engagements of Christian theology with economics.